Cultura e movimentos sociais à luz do materialismo histórico-dialético de Gramsci: um estudo sobre os movimentos sociais de cultura de Sorocaba/SP - Bergamini, Débora (2018)
The present work was developed according to the methodology of bibliographical, documentary and field research. It aims to investigate the projects and actions in the area of education accomplished by the social movements of culture of the region of Sorocaba / SP, in order to reveal if the praxis of these movements can collaborate with the fight for the construction of another hegemony. To do so, the text begins with a discussion of the multiplicity of the concept of culture and the dichotomy between postmodern and Marxist perspectives in the study of the term. This debate continues guided by the Gramscian Marxist approach, in order to present the culture from the historical-dialectical materialist paradigm. In the sequence, the concept of social movements is discussed, presenting studies on the history of social movements in Latin America, the conceptualization of social movements of culture, a discussion about the limits existing in the so-called theory of new social movements and ends with the exercise of to approach social movements in the light of historical-dialectical materialism, according to the Gramscian perspective. In the third and final chapter is the analysis of education projects carried out by the social movements of culture of Sorocaba / SP, where it is evident that the praxis of these movements, which in general are not oriented by a centrality in the class debate, , yet an important instrument in the struggle for overcoming the capitalist mode of production. In the conclusion, it is evident the need of interpretations of the term culture that transpose those that designate the concept only as a mere reflection of the material relations, just as it also demonstrates the still incipient character of the studies on the social movements in the light of historical materialism suggesting that advances in this field of study may reveal the impacts of social movements on concrete reality.